Lung injury and respiratory mechanics in rugby union - Lindsay, A.; Bernard, A.; Davidson, S. M.; Redmond, D. P.; Chiew, Y. S.; Pretty, C.; Chase, J. G.; Shaw, G. M.; Gieseg, S. .; Draper, N. (The Journal of Sports Medicine and Physical Fitness, 2016)
BACKGROUND: Rugby is a highly popular team contact sport associated with high injury rates. Specifically, there is a chance of inducing internal lung injuries as a result of the physical nature of the game. Such injuries are only identified with the use of specific invasive protocols or equipment. This study presents a model-based method to assess respiratory mechanics of N=11 rugby players that underwent a low intensity experimental Mechanical Ventilation (MV) Test before and after a rugby game.